Alemtuzumab and sirolimus in renal transplantation: six-year results of a single-arm prospective pilot study. - Sutherland, A; Akhtar, M; Zilvetti, M; Brockmann, J; Ruse, S; Fuggle, S; Sinha, S; Harden, P; Friend, P (2014)
mTOR inhibitors avoid calcineurin nephrotoxicity, but sirolimus de novo is associated with unacceptable side effects and higher rejection rates. We have investigated a modified strategy: alemtuzumab induction with tacrolimus and mycophenolate maintenance, switching from tacrolimus to sirolimus at 6 months and stopping mycophenolate at 12 months. Here, we report the 6-year follow-up of 30 patients prospectively recruited to this single-arm pilot study and compare outcomes to a matched contemporaneous control group of 30 patients who received standard induction and calcineurin-inhibitor-based immunosuppression.Six-year patient and graft survival were 83% and 80%(alemtuzumab) versus 77% and 70% (control). Rejection rates in the first 6 months were similar in alemtuzumab (6.6%) and control groups (10%). A higher than expected incidence of rejection in the alemtuzumab group following cessation of mycophenolate at 1 year (17%) was mitigated in later patients by retaining low dose mycophenolate. Mean eGFR was higher in the alemtuzumab group at all time points but not significantly (p¼0.16). Tacrolimus levels in the first 6 months were significantly higher in the contemporaneous control group (p<0.001). Alemtuzumab induction with initial treatment with tacrolimus enables conversion to sirolimus without the side effects and incidence of acute rejection seen in earlier protocols.